2014
DOI: 10.1186/bf03353342
|View full text |Cite
|
Sign up to set email alerts
|

Pseudotachylytes, related fault rocks, asperities, and crustal structures in the Hidaka metamorphic belt, Hokkaido, northern Japan

Abstract: Many pseudotachylytes and their related fault rocks are found in the Hidaka metamorphic belt representing an ancient crustal section. On the basis of field observations of the pseudotachylytes and related fault rocks, nature of seismogenic faulting in the Hidaka crust is examined. The field observations suggest the following conclusions.(1) Two structural types of pseudotachylytes are distinguished: layer-parallel and layer-oblique. The latter are scattered in the metamorphic belt, but the former occur only in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Melting and fluidization seems to be the main mechanisms of dynamic weakening of shear zones at this depth [ Tanaka et al , 2001c; Ohtsuki et al , 2003]. Similar occurrences of deep shear zones are also recognized in Hidaka metamorphic zones, northern Japan [ Toyoshima et al , 2004; Tanaka et al , 2004; Shimada et al , 2004]. Fracture zones became greatly widened at the middle depth of the crust, associated with the precipitation of zeolite (stage II shear zones).…”
Section: Discussionmentioning
confidence: 77%
“…Melting and fluidization seems to be the main mechanisms of dynamic weakening of shear zones at this depth [ Tanaka et al , 2001c; Ohtsuki et al , 2003]. Similar occurrences of deep shear zones are also recognized in Hidaka metamorphic zones, northern Japan [ Toyoshima et al , 2004; Tanaka et al , 2004; Shimada et al , 2004]. Fracture zones became greatly widened at the middle depth of the crust, associated with the precipitation of zeolite (stage II shear zones).…”
Section: Discussionmentioning
confidence: 77%
“…Subsequently, localized low-temperature mylonitization related to the intrusion of sheet like tonalites and brittle deformations took place during retrograde metamorphism. Koyasu et al (2006Koyasu et al ( , 2007 also summarized that most of the deformation events in the upper sequence and tonalite in the study area cannot be correlated with those of the lower sequence events reported by Toyoshima et al (2004).…”
Section: Geological Settingmentioning
confidence: 72%
“…4c, e). We consider these brittle fault rocks to be comparable to the stage III fault rocks of Toyoshima et al (1997Toyoshima et al ( , 2004, because of their similar modes of occurrence, deformation types, orientation, and metamorphic conditions.…”
Section: Occurrence Of Host Metamorphic Rocks and Fault Rocksmentioning
confidence: 98%
See 2 more Smart Citations